Monthly high-dose vitamin D supplementation does not increase kidney stone risk or serum calcium: results from a randomized controlled trial. Issue 6 (21st April 2019) - Malihi, Zarintaj; Lawes, Carlene M M; Wu, Zhenqiang; Huang, Ying; Waayer, Debbie; Toop, Les; Khaw, Kay-Tee; Camargo, Carlos A; Scragg, Robert
ABSTRACT: Background: A growing number of randomized controlled trials (RCTs) are investigating the potential health benefits of high-dose vitamin D supplementation. However, there are limited RCT data on the safety of calcium-related adverse effects. Objective: We investigated the incidence of kidney stone and hypercalcemia events in a large, population-based RCT of vitamin D supplementation. Design: The Vitamin D Assessment (ViDA) study was a randomized, double-blind, placebo-controlled trial of vitamin D supplementation in 5110 participants in Auckland, New Zealand. This trial investigated the impact of monthly 100, 000 IU vitamin D3 supplementation over several years on cardiovascular events, respiratory infections, and falls/fractures. Participants provided information about recent kidney stone events in regular questionnaires sent to them with study capsules. Hospitalization data for kidney stones were collected from health authorities. Serum calcium was measured in an 8% subsample of participants who returned annually for blood tests. HRs of time to the first kidney stone event were calculated by Cox regression. Results: During a median follow-up of 3.3 y, 158 participants reported a kidney stone event (76 vitamin D, 82 placebo). The HR of reporting the first kidney stone event was 0.90 (95% CI: 0.66, 1.23; P  = 0.51) for participants in the vitamin D arm compared with the placebo arm. There were 18 urolithiasis events in the hospitalization records: 7 in the vitamin D arm and 11 from the placebo arm. The HR to the first hospitalization urolithiasis event was 0.62 (95% CI: 0.24, 1.26; P  = 0.30) in the vitamin D arm compared with the placebo arm. From the subsample annual blood test, there was no case of hypercalcemia in the vitamin D arm, compared with 1 in the placebo arm. Conclusion: Over a median of 3.3 y, monthly supplementation with 100, 000 IU vitamin D3 did not affect the incidence rate of kidney stone events, or hypercalcemia. This study was registered at clinicaltrials.gov as ACTRN12611000402943.